An evaluation of the antioxidant properties of iodinated radiographic contrast media: An in vitro study - Montree Tungjai; Singhadeth Sukantamala; Pimchanok Malasaem; Nathupakorn Dechsupa; Suchart Kothan (Toxicology Reports, 2018)
This study reveals the antioxidant properties of iodinated radiographic contrast media to be used in diagnostic radiology. Di(phenyl)-(2,4,6-trinitrophenyl) iminoazanium (DPPH), ferric reducing ability of plasma (FRAP), and 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) assays were used for determining in vitro the antioxidant properties of five iodinated radiographic contrast media such as iobitridol (xenetix), iodixanol (visipaque), iohexol (omnipaque), ioxaglate (hexabrix), and isovue (iopamiro). An ascorbic acid and Trolox solution served as a positive control. The absorbance intensity of the colored product was recorded using a spectrophotometer. For DPPH and ABTS assay, the absorbance intensity at 533 and 752 nm, respectively was decreased when compared to control; it indicated an increase in antioxidant activity. For FRAP assay, the absorbance intensity at 593 nm was increased when compared to control; it indicated an increase in antioxidant activity. The results showed that five iodinated radiographic contrast media did not differ in DPPH• radical-scavenging activity when compared to a corresponding control. The ferric reducing ability of all of these iodinated radiographic contrast media also did not differ when compared to a corresponding control, except for iobitridol at 200 mgI/mL and ioxaglate at 50–200 mgI/mL. All iodinated radiographic contrast media showed ABTS•+ radical-scavenging activity. This finding suggested that iobitridol, iodixanol, iohexol, ioxaglate, and isovue exhibited weak in vitro antioxidant properties. The antioxidant ability depended on the type of free radical production and the concentration of iodinated radiographic contrast media. Keywords: Antioxidant property, Radiographic contrast media, Free radical